SURVEI KETERLAKSANAAN PEMBELAJARAN PJOK SECARA DARING PADA MASA PANDEMI COVID-19 DI SEKOLAH NEGERI DAN SEKOLAH SWASTA (STUDI PADA GURU PJOK SMA NEGERI 15 BANDUNG DAN GURU PJOK SMA KARTIKA SILIWANGI 2) - Rizki Ahmad Yusron, - (2022)
The purpose of this study is to find out the teaching and learning process, content / materials, and learning methods during pandemics in public schools and private schools. Research methods use descriptive research with a quantitative approach. The population in this study is the teacher at SMAN 15 Bandung and Kartika Siliwangi High School 2. In the sampling of this study were 2 teachers from public schools and 2 teachers from private schools with saturated sampling techniques. Instruments use teaching and learning process questionnaires, content / materials, and learning methods. The process of learning to teach online during the Covid-19 pandemic in public schools the highest value is the value of the behavior / motivation aspect of students and the lowest value is the value of the support aspect of environmental factors. While in private schools the highest is the value of the aspect of behavior / motivation of students and interaction of teachers and students, and the lowest is the value of the aspect of behavior / verbal teacher. Online learning materials during the Covid-19 pandemic in public schools and private schools the highest grades are grades from the physical fitness activity aspect and the lowest value is the value of the aspect of aquatic activity. Online learning methods during the Covid-19 pandemic in public schools the highest value is the value of the management strategy aspect and the lowest value is the value of the organizing strategy aspect. While in private schools the highest value is the value of the aspect of organizing strategy and delivery strategy, and the lowest value is the value of the management strategy aspect. The results also showed there was no difference between the implementation of online PJOK learning during the Covid-19 pandemic in Public Schools and Private Schools with a error rate of 5% then obtained utabel (6.6) is 5 while the minimum value of Uhitung is 17, then with a error rate of 5% obtained by comparison of Uhitung > Utabel (17>5).